Larvas de Glyphipteryx sp. (Lepidoptera: Glyphipterygidae), en agallas de Hyptis urticoides (Lamiales: Labiatae) - Calvo, Renán (Universidad de Costa Rica, 1993)
In Costa Rica, gall development is induced in stems of Hyptis urticoides (Labiatae) by an unidentified microlepidopteran of the genus Glyphipteryx (Glyphipterydidae). Prepupae are formed in 40 days. A single omice elosed with silk is used for penetration, elimination of meconium and emergence. Larvae experimentally transfcned to non-stem tissue can develop but do not produce a gallo.